Gestión logística de la Empresa Jorua S.A. - Gómez Bajaña, Delia Karina (2019)
The present case study developed based on the study of the logistics management of the Jorua Importer in the city of Babahoyo, is carried out based on the parameters of the quantitative research and under the research sub-line: “administrative management model. The objective of this case was to: Analyze the logistic processes that are executed in order to detect the shortcomings and deficiencies that arise from the logistics management in the importer. The results obtained from the investigation were the following: deficiencies in the control of inventories, certain sales are not used or the forecast was also mentioned, lack of a logistic procedures manual, care of an accounting management software and integral logistics